Second language writing anxiety, computer anxiety, and performance in a classroom versus a web-based environment - Dracopoulos, Effie (Zakład Filologii Angielskiej: Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2011)
This study examined the impact of writing anxiety and computer anxiety on language learning for 45 ESL adult learners enrolled in an English grammar and writing course. Two sections of the course were offered in a traditional classroom setting whereas two others were given in a hybrid form that in-volved distance learning. Contrary to previous research, writing anxiety showed no correlation with learning performance, whereas computer anxie-ty only yielded a positive correlation with performance in the case of class-room learners. There were no significant differences across learning envi-ronments on any measures. These observations are discussed in light of the role computer technologies now play in our society as well as the merging of socio-demographic profiles between classroom and distance learners. Our data suggest that comparisons of profiles between classroom and distance learners may not be an issue worth investigating anymore in language stud-ies, at least in developed countries.
Keywords: Writing anxiety; Computer anxiety; Second language learning; ESL; Distance learning